The Effectiveness of the Community Learning Service Model Development Through the Literacy Clinic (Lembaga Pengembangan Kinerja Dosen, 2025)
The government has implemented various illiteracy eradication programs at both central and local levels. However, illiteracy remains high, with South Sulawesi ranking sixth nationally. This condition is influenced by the imbalance between the number of Non-Formal Education Units and target areas, limited human resources, as well as learner-related factors such as motivation, age, occupation, distance to learning sites, and monotonous teaching methods. Community learning services through literacy clinics using collaborative methods Reading, Writing Beginning, Structure, Analysis, and Synthesis, combined with project-based learning serve as alternative models to increase community participation and improve learning outcomes. The problem of this research is how the description of the implementation of basic literacy programs through the model